Barriers and facilitators to implementation of menu labelling interventions to support healthy food choices: a mixed methods systematic review protocol - Claire Kerins (Systematic Reviews, 2018)
Abstract Background Menu labelling is continuing to gather public and legislative support as one of the potential environmental strategies for addressing the obesity pandemic. However, issues relating to implementation have been reported in countries where menu labelling has been introduced on a voluntary or mandatory basis. The aim of this mixed methods systematic review is to synthesise the empirical evidence on the barriers and facilitators to implementation of menu labelling interventions to support healthy food choices. Methods This review will use the ‘best fit’ framework synthesis approach to synthesise qualitative, quantitative and mixed methods evidence. Peer-reviewed publications will be accessed through PubMed, EMBASE, CINAHL, PsycINFO, Web of Science and Scopus. Grey literature will be accessed through Google Scholar, OpenGrey, RIAN, EThOS, ProQuest, WorldCat, Networked Digital Library of Theses and Dissertations, Open Access Theses and Dissertations, and public health organisation websites. Screening reference lists, citation chaining and contacting authors of all included studies will be undertaken. There will be no restriction on menu labelling scheme or format, publication year or language; however, only primary research studies relevant to supply-side stakeholders will be eligible for inclusion. Study quality will be assessed using the Mixed Methods Appraisal Tool. At least two independent reviewers will perform study selection, data extraction and quality appraisal; if consensus is required, another independent reviewer will be consulted. A combination of deductive coding, using the Consolidated Framework for Implementation Research as the a priori framework, and inductive analysis, using secondary thematic analysis, will be used. The overall process will assist in the construction of a new evidence-based conceptual model regarding the implementation of menu labelling interventions. The new model will be assessed for bias and a sensitivity analysis performed. Discussion Given the growing consensus that a systemic, sustained portfolio of obesity prevention strategies, delivered at scale, is needed to address the obesity epidemic, greater understanding of the practical issues relating to implementation of such strategies is required. Findings from this review will be used to develop a set of best-practice guidelines to enhance the adoption, implementation and sustainability of menu labelling interventions across countries worldwide. Systematic review registration PROSPERO CRD42017083306